Mapping levels of COVID-19 vaccine hesitancy worldwide: preliminary results of a systematic review. (20th October 2021) - Massimi, A; Renzi, E; Baccolini, V; De Vito, C; Migliara, G; Marzuillo, C; Villari, P
Abstract: Background: Several factors can determine the success of a vaccination campaign, regardless of the availability of an effective and safe vaccine. Among these, vaccine hesitancy (VH) has long represented one of the main barriers to achieving vaccination coverage goals in many countries. The aim of this systematic review was to summarize the global levels of COVID-19 VH and to identify their determinants. Methods: A systematic review of the literature was carried out following the PRISMA guideline and searching on PubMed, Web of Science, Scopus and PsycINFO for observational studies published up to April 2021 in English or Italian language. Levels of hesitancy and data on determinants, according to the SAGE working group matrix of determinants, were extracted. The systematic review protocol was registered on Prospero (ID: CRD42021235328). Results: Of the 5447 articles initially retrieved, 89 were included in the qualitative synthesis. The included studies investigated COVID-19 VH on 1.954.331 individuals from 68 different countries (North America 19; South America 23; Africa 3; Asia 18; Europe 55; Oceania 4) between March 2020 and January 2021. Rates of hesitancy, before to the worldwide availability of vaccinations (82 studies), ranged from 84.6% (Cameroon, May-August 2020) to 10.37% (China, March-June 2020). Studies carried out on January 2021 (N = 7) showed rates ranging from 42.8% (Turkey) to 5.3% (UK). A subgroup analysis of data referring to healthcare workers showed the highest hesitancy rates in Honk Kong (60%) and Turkey (26.6%), before and after vaccine availability, respectively. Conclusions: Preliminary results confirm the wide variability of VH across the world. The ongoing quantitative synthesis on prevalence of VH and the analysis on determinants will allow to update intervention strategies to address VH, both in general population and healthcare workers, orienting public health policies. Key messages: Vaccine Hesitancy continues to be one of the greatest threats to global health and, in the long term, one of the potential barriers to the success of the global COVID-19 vaccination campaign. Identifying and synthesizing the specific determinants of COVID-19 vaccine hesitancy is essential to guide intervention strategies to promote vaccine confidence and, finally, vaccine acceptance.